DETERMINASI KONFUSIANISME DALAM ANALISIS WACANA KRITIS NOVEL KLASIK “JOURNEY TO THE WEST” - Melinda Rahmawati; Yustiara Nuraini; Bimo Rafi Widianto; Debi Robi Yanti; Sulaeman Sulaeman (Universitas Sebelas Maret, 2021)
The purpose of research to see the determination formed by Confucianism in critical discourse analysis of the classic novel